A new 4x4 wide-sense nonblocking photonic switching network - Suliman, F. M.; Mohammad, A. B.; Seman, K. (2001)
In this paper, new switch architecture is proposed for nonblocking photonic switching. This switch is a 4x4 space division multistage network using 2x2 optical switch elements, which may be directional couplers, fabricated on titanium diffused lithium niobate (Ti: LiNb03) substrates. The idea behind the architecture is presented and some properties of the switch are derived and analyzed. The performance of the switch is also discussed and compared with other well-known designs.